2021
DOI: 10.1021/acssuschemeng.1c07217
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Felt-Sandwiched Ni/SiC Catalysts for the Induction Versus Joule-Heated Sabatier Reaction: Assessing the Catalyst Temperature at the Nanoscale

Abstract: The paper describes a series of graphite felt (GF)-sandwiched k Ni/SiC composites at variable metal loading (k = 10, 15 and 20 wt.%) and their application as catalysts for the CO 2 methanation process (Sabatier reaction) under two distinct and conceptually different heating setup: Joule heating vs. Induction heating. A comparative analysis carried out on all catalysts from this series operated under the two heating configurations, has unveiled the superior performance of radiofrequency heated (IH) catalysts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
4
11
0
Order By: Relevance
“…The temperature differences noted here for 5Ni/TiO 2 are in the range of temperature differences reported for 10Ni/SiC systems in the literature by Truong-Phuoc et al [39]. In the literature, Pham-Huu and their co-workers have thoroughly investigated the catalytic CO 2 methanation performances (% CO 2 conversion, % CH 4 selectivity versus temperature) under both induction heating and classical heating conditions [22,38,39,41]. It was reported that, at a given temperature, the catalytic % CO 2 conversion and %CH 4 selectivity values were higher for induction heating conditions than for classical heating.…”
Section: Catalytic Performancessupporting
confidence: 77%
See 2 more Smart Citations
“…The temperature differences noted here for 5Ni/TiO 2 are in the range of temperature differences reported for 10Ni/SiC systems in the literature by Truong-Phuoc et al [39]. In the literature, Pham-Huu and their co-workers have thoroughly investigated the catalytic CO 2 methanation performances (% CO 2 conversion, % CH 4 selectivity versus temperature) under both induction heating and classical heating conditions [22,38,39,41]. It was reported that, at a given temperature, the catalytic % CO 2 conversion and %CH 4 selectivity values were higher for induction heating conditions than for classical heating.…”
Section: Catalytic Performancessupporting
confidence: 77%
“…Furthermore, with the low Ni loading and high heating capabilities of iron wool, the actual surface temperature of the Ni nanoparticles is perhaps slightly underestimated. The temperature differences noted here for 5Ni/TiO 2 are in the range of temperature differences reported for 10Ni/SiC systems in the literature by Truong-Phuoc et al [39]. In the literature, Pham-Huu and their co-workers have thoroughly investigated the catalytic CO 2 methanation performances (% CO 2 conversion, % CH 4 selectivity versus temperature) under both induction heating and classical heating conditions [22,38,39,41].…”
Section: Catalytic Performancessupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, it can avoid the thermal decomposition of the reactants or intermediate compounds caused by overheating of the whole reactor [5,6]. Recently, IH mode has been reported as an efficient heating mode for operating catalytic processes with significant improved performance [6][7][8][9][10][11]. Alongside with the advantages cited above IH also represents a green heating mean for operating catalytic processes as it can be operated using exceeding renewable electricity, instead of using traditional fuel burner for providing heat to the reactor, which contributes to the reduction of CO2 for the process [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recently, the IH mode has been reported as an efficient heating mode for operating catalytic processes with significantly improved performance. [6][7][8][9][10][11] Besides the abovementioned advantages, IH represents a green heating means for operating catalytic processes, as it can be operated using exceeding renewable electricity, instead of using a traditional fuel burner for providing heat to the reactor, which contributes to the reduction of CO 2 for the process. 6,12,13 Hydrogen sulfide (H 2 S), one of the major toxic and malodorous gases, is commonly emitted from chemical industries, such as natural gas refineries, crude oil, biogas purification and coal chemistry.…”
Section: Introductionmentioning
confidence: 99%